Pengaruh Desain Produk Citra Merek Dan Pengalaman Pelanggan Terhadap Keputusan Pembelian Roti’o Di Kota Batam - Rintan, Rintan; Suhardi, Suhardi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effect of product design, brand image, and customer experience on purchasing decisions of Roti’O products in Batam City. This research employs a quantitative approach with a causal associative method. The population consists of consumers who have purchased Roti’O products in Batam City, with a sample of 204 respondents selected using purposive sampling. Data were collected through questionnaires using a Likert scale and analyzed using SPSS version 31. The data analysis methods include validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination, as well as hypothesis testing using t-test and F-test. The results indicate that product design, brand image, and customer experience partially have a positive and significant effect on purchasing decisions of Roti’O in Batam City. Simultaneously, these three variables also have a positive and significant effect on purchasing decisions. This study is expected to provide useful insights for companies in developing effective marketing strategies.